IL-31: A new link between T cells and pruritus in atopic skin inflammation - Sonkoly, Eniko; Muller, Anja; Lauerma, Antti I.; Pivarcsi, Andor; Soto, Hortensia; Kemeny, Lajos; Alenius, Harri; Dieu-Nosjean, Marie-Caroline; Meller, Stephan; Rieker, Juliane; Steinhoff, Martin; Hoffmann, Thomas K.; et al. (Journal of Allergy and Clinical Immunology, 2006)
IL-31 is a novel T-cell–derived cytokine that induces severe pruritus and dermatitis in transgenic mice, and signals through a heterodimeric receptor composed of IL-31 receptor A and oncostatin M receptor. To investigate the role of human IL-31 in pruritic and nonpruritic inflammatory skin diseases. The expression of IL-31 was analyzed by quantitative real-time PCR in skin samples of healthy individuals and patients with chronic inflammatory skin diseases. Moreover, IL-31 expression was analyzed in nonlesional skin of atopic dermatitis patients after allergen or superantigen exposure, as well as in stimulated leukocytes. The tissue distribution of the IL-31 receptor heterodimer was investigated by DNA microarray analysis. IL-31 was significantly overexpressed in pruritic atopic compared with nonpruritic psoriatic skin inflammation. Highest IL-31 levels were detected in prurigo nodularis, one of the most pruritic forms of chronic skin inflammation. In vivo, staphylococcal superantigen rapidly induced IL-31 expression in atopic individuals. In vitro, staphylococcal enterotoxin B but not viruses or T H1 and T H2 cytokines induced IL-31 in leukocytes. In patients with atopic dermatitis, activated leukocytes expressed significantly higher IL-31 levels compared with control subjects. IL-31 receptor A showed most abundant expression in dorsal root ganglia representing the site where the cell bodies of cutaneous sensory neurons reside. Our findings provide a new link among staphylococcal colonization, subsequent T-cell recruitment/activation, and pruritus induction in patients with atopic dermatitis. Taken together, these findings show that IL-31 may represent a novel target for antipruritic drug development.